Blood ties : the labyrinth of family membership in long term adoption reunion : a thesis presented in partial fulfilment of the requirements for the degree of Master of Arts in Social Anthropology at Massey University - Browning, Julee A (Massey University, 2005)
This thesis reports original research conducted with twenty adoptees, adopted under closed-stranger protocols, who have been experiencing regular post-reunion contact with their birth families for more than ten years. It examines the themes of the mothering role, family obligation and family membership to uncover how adoptees navigate their family membership within and between two families (adoptive and birth family). This study presents the thoughts, feelings and observations of the participants in their own words to convey a deeper understanding of their experiences. Drawing upon in-depth interviews, this study has sought to expand on earlier research focusing on the search and reunion and immediate post-reunion stages to examine the long-term experiences of adoptees in post-reunion. The principal finding is that reunited relationships have no predictable pathways and are approached with varying levels of ambivalence and emotional strain, and that there is no fixed pattern of family arrangements and relational boundaries. While closed-stranger adoptions and the subsequent reunions may eventually cease, this research may assist in understanding the issues surrounding the reunion between gamete (egg) and sperm donor's and their offspring in the future. KEYWORDS: Adoption Post-reunion, Adoptee, Birth Family, Family Membership, Family Relationships, Closed Adoption Reunion.
Keywords: New Zealand; Adoption; Birthmothers; Adoptive parents; Adoptees; Family